The Influence of Management Accounting Information System Characteristics, Decentralization, and Budgetary Participation on Managerial Performance at PT. Sinar Supermarket in Surabaya - Siswohadi; Andrik Gastri Widjatmiko; Ayi Hendriawan; Shafira Aulia Rahma (International Journal of Economics, Science, and Education, 2025)
This research aims to analyze the influence of management accounting information system characteristics, decentralization, and participation in budget preparation on managerial performance at PT. Sinar Supermarket in Surabaya. This research uses a quantitative approach with an explanatory research design. Data was obtained through distributing questionnaires to managers in various divisions of PT. Sinar Supermarket. The data analysis technique used is multiple linear regression to test the influence of the independent variable on the dependent variable with the SPSS version 16 program. The conclusion of this study provides evidence that the characteristics of management accounting system information, decentralization, and participation in budget preparation play an important role in improving managerial performance. Therefore, companies are advised to pay attention to these factors in planning and implementing managerial strategies to increase operational effectiveness and efficiency.